Values of income and turnover tax rates and effective tax burdens borne by consumers - Biernacki, Krzysztof (Stawki podatków dochodowych oraz obrotowych a efektywne opodatkowanie konsumentów, 2011)
Every transaction is burdened with income tax and turnover tax, which are complementary to each other. Thus, the total tax burden should be perceived as a sum of them. The complementary relation is for many tax-specialists the main reason of existence of the progressive scale in income taxes. The regressive nature of the tax rates in VAT is to minimise the negative impact of this progression. This paper, however, shows that calculations do not sustain these assumptions. The taxpayers do not spend all their income, and therefore the compensation of the regressive scale of the VAT rates works to a certain amount. Above this limit, the income tax progression substantially increases the effective rate of taxation. Drawing on the present calculations, it may be concluded that the progression of income taxes cannot be justified by the complementary character of VAT
Nauki o Finansach = Financial Sciences, 2011, Nr 1 (6), s. 56-66
Keywords: taxes; income taxes; value added tax